2022
DOI: 10.1002/joa3.12685
|View full text |Cite
|
Sign up to set email alerts
|

Early evaluation of atrial high rate episodes using remote monitoring in pacemaker patients: Results from the RAPID study

Abstract: Aim Remote monitoring (RM) of implantable cardiac devices has enabled continuous surveillance of atrial high rate episodes (AHREs) with well‐recognized clinical benefits. We aimed to add evidence on the role of the RM as compared to conventional follow‐up by investigating the interval from AHRE onset to physician’s evaluation and reaction time in actionable episodes. Methods and Results A total of 97 dual‐chamber pacemaker recipients were followed with RM (RM‐ON group; N = 64) or conventional in‐office visits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In the prospective, non-interventional RAPID study the median evaluation delay for AHREs for the pacemaker patient group with remote monitoring on (RM-ON) was 79 days shorter than for the patient group with remote monitoring off (RM-OFF). In addition, therapy adjustments occurred 77 days earlier in the RM-ON group and there were 50 % less in-office visits compared to the RM-OFF group [8] . The randomized COMPAS trial showed similar results.…”
Section: Introductionmentioning
confidence: 86%
“…In the prospective, non-interventional RAPID study the median evaluation delay for AHREs for the pacemaker patient group with remote monitoring on (RM-ON) was 79 days shorter than for the patient group with remote monitoring off (RM-OFF). In addition, therapy adjustments occurred 77 days earlier in the RM-ON group and there were 50 % less in-office visits compared to the RM-OFF group [8] . The randomized COMPAS trial showed similar results.…”
Section: Introductionmentioning
confidence: 86%
“…We suppose that it played an important role in the high sense of safety that resulted from our questionnaires. Despite clinical benefits, remote monitoring requires an increased work overload to physicians, nurses, and hospital stuff to check regularly automatic transmissions and to communicate with families during follow-up if symptoms occur or arrhythmias are detected [17][18][19]. More studies are required to better assess the impact of remote monitoring on the early detection of arrhythmias and the symptom-rhythm correlation in the pediatric population.…”
Section: Remote Monitoringmentioning
confidence: 99%
“…1 This approach safely reduces the burden of inoffice visits while ensuring early detection of arrhythmias and adverse events. 2 RM of implantable cardiac monitors (ICMs) in patients with unexplained syncope has been shown to facilitate the timely recognition of asymptomatic cardiac arrhythmias. [3][4][5] However, a significant challenge of this strategy may be the high volume of transmissions received by the device clinic, which requires resources for timely review.…”
Section: Introductionmentioning
confidence: 99%
“…Remote monitoring (RM) is recommended as part of the standard follow‐up management strategy for patients with cardiac implantable electronic devices 1 . This approach safely reduces the burden of in‐office visits while ensuring early detection of arrhythmias and adverse events 2 . RM of implantable cardiac monitors (ICMs) in patients with unexplained syncope has been shown to facilitate the timely recognition of asymptomatic cardiac arrhythmias 3–5 .…”
Section: Introductionmentioning
confidence: 99%